Conflict Management in Illicit Drug Cryptomarkets - Morselli, Carlo (International criminal justice review, 2017)
Illegal drug markets have been described as “stateless” systems. Drug dealers, moreover, are commonly considered to have a predilection toward the use of violence to resolve disputes arising from dealing activities. While some studies have undermined this popular perception, new trends surrounding the distribution of illegal drugs via online channels (drug cryptomarkets) have shifted the transactional setting from the physical to virtual realm, thus decreasing the likelihood of violent resolution outcomes even further. This article examines conflict management strategies within cryptomarkets by coding discussion forums between vendors and buyers. Violence, as expected, is absent. Strategies more likely reflect alternatives that have been recognized in conflict management research within and beyond illegal market settings: tolerance, avoidance, ostracism, third-party intervention, negotiation, and threats. The overall setting from which such resolutions emerge is clearly not subject to formal regulations, but our analyses illustrate the multitude of informal social control mechanisms that are consistently at play and which underlie the self-regulatory and communal processes that are firmly in place.